Perceptions on smoking cessation counselling competency among Malaysian pharmacy undergraduates: A preliminary study - Simansalam, Saraswathi; Nik Mohamed, Mohamad Haniki (International Pharmaceutical Federation, 2017)
Background: There is a paucity of literature pertaining to smoking cessation counselling among Malaysian pharmacy students.